Recent advances in negative ion mass spectrometry. - Bowie, J H (1980)
The paper describes theoretical and applied applications of negative ion chemistry carried out at Adelaide during the past five years. kinetic energy release in negative metastable ion decompositions is described, with particular reference to simple cleavage reactions, rearrangement reactions, and reactions which proceed by dual mechanisms. The application of deuterium isotope effects as a mechanistic probe is illustrated by reference to the elimination of ketene from quinone acetate negative ions. Charge stripping of a negative ion yields a decomposing positive ion, which produces a dissociative charge inversion spectrum of the negative ion. This technique allows the study of positive ions not available by conventional ionization; it provides a fingerprint for the parent positive ion produced in the collision process, and it may be used to determine the structure of the precursor negative ion. Finally, a combination of a negative ion spectrum and a charge inversion spectrum may be used as an analytical technique for the structure determination of unknown molecules.